FC colour images of dwarf planet Ceres reveal a complicated geological history. (1st December 2016) - Nathues, A.; Hoffmann, M.; Platz, T.; Thangjam, G.S.; Cloutis, E.A.; Reddy, V.; Le Corre, L.; Li, J.-Y.; Mengel, K.; Rivkin, A.; Applin, D.M.; Schaefer, M.; et al.
Abstract: The dwarf planet Ceres (equatorial diameter 963km) is the largest object that has remained in the main asteroid belt (Russell and Raymond, 2012 ), while most large bodies have been destroyed or removed by dynamical processes (Petit et al. 2001; Minton and Malhotra, 2009 ). Pre-Dawn investigations (McCord and Sotin, 2005; Castillo-Rogez and McCord, 2010 ;Castillo-Rogez et al., 2011 ) suggest that Ceres is a thermally evolved, but still volatile-rich body with potential geological activity, that was never completely molten, but possibly differentiated into a rocky core, an ice-rich mantle, and may contain remnant internal liquid water. Thermal alteration should contribute to producing a (dark) carbonaceous chondritic-like surface (McCord and Sotin, 2005; Castillo-Rogez and McCord, 2010 ;Castillo-Rogez et al., 2011 ;Nathues et al., 2015 ) containing ammoniated phyllosilicates (King et al., 1992 ;De Sanctis et al., 2015 and 2016 ). Here we show and analyse global contrast-rich colour mosaics, derived from a camera on-board Dawn at Ceres (Russell et al., 2016 ). Colours are unexpectedly more diverse on global scale than anticipated by Hubble Space Telescope (Li et al., 2006 ) and ground-based observations (Reddy et al. 2015 ). Dawn data led to the identification of five major colour units. The youngest units identified by crater counting, termed bright and bluish units, are exclusively found at equatorial and intermediate latitudes. We identified correlations between the distribution of the colour units, crater size, and formation age, inferring a crustal stratigraphy. Surface brightness and spectral properties are not correlated. The youngest surface features are the bright spots at crater Occator (~Ø 92km). Their colour spectra are highly consistent with the presence of carbonates while most of the remaining surface resembles modifications of various types of ordinary carbonaceous chondrites.